If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x) + 2x + -24 = 0 Multiply x * x x2 + 2x + -24 = 0 Reorder the terms: -24 + 2x + x2 = 0 Solving -24 + 2x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-6 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-6, 4}
| -(5y+1)-(-4-3)=0 | | 32y^9+4y^4= | | 4x^2+144=0 | | 6w^2+23w+20=0 | | 2x^2+13x+16=-5 | | 3x=(4)+(x-2) | | 2(9-5)-(3a+1)=0 | | ax+ay=a(x+y) | | 4x^2-12=13 | | 2/3n-5/8-2 | | 12(3x-1)=3(12x+6) | | 6+3r-3=8r+11-4r | | 4(7-2)= | | log(4x)+log(9x)=2 | | 4x-2(x-1)+5= | | 2r^3+14r^2-36r=0 | | 2x-5*(x+3*(3-x))= | | 7x-12-12x= | | 5(x-6)=55/11 | | -12.4=19.1+n/-7.9 | | n+3n+4n=100 | | 2w+2(w+10)=28 | | x+4x=258 | | 5640/9.4 | | 18p-45=o | | In(x+2)+in(x-2)=7 | | 3x+x=360 | | In(x)+in(x+1)=2 | | In(x)+in(x+1)=12 | | 9(x+9)=134 | | 1/4+5/12 | | 4n^2=6 |